Surname Inherited Algorithm Research Based on Artificial Immune System - Jing Xie; Yaobin Hu; Huiling Zhu; Yulin Wang (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
To keep the diversity of antibodies in artificial immune system evolution process, this paper puts forward a kind of increase simulation surname inheritance algorithm based on the clonal selection algorithm, and identification and forecast the Vibration Data about CA6140 horizontal  lathe machining slender shaft workpiece prone . The results show that the algorithm has the characteristics of flexible application, strong adaptability, an effective approach to improve efficiency of the algorithm, a good performance of global searching and broad application prospect. DOI: http://dx.doi.org/10.11591/telkomnika.v11i6.2668